2007
DOI: 10.1111/j.1462-2920.2007.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Extremely acidic, pendulous cave wall biofilms from the Frasassi cave system, Italy

Abstract: The sulfide-rich Frasassi cave system hosts an aphotic, subsurface microbial ecosystem including extremely acidic (pH 0-1), viscous biofilms (snottites) hanging from the cave walls. We investigated the diversity and population structure of snottites from three locations in the cave system using full cycle rRNA methods and culturing. The snottites were composed primarily of bacteria related to Acidithiobacillus species. Other populations present in the snottites included Thermoplasmata group archaea, bacteria r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 37 publications
9
116
0
5
Order By: Relevance
“…Thus, some archaeal groups in sludge, such as Thermoprotei and Thermoplasmata, may be better able to colonize onto the membrane during the initial stage of biofilm development. In previous studies, the Thermoprotei and Thermoplasmata have also been detected to form the biofilms in many different environmental sites, such as sulfide-rich cave wall (Macalady et al, 2007), acid mine drainage system (Justice et al, 2012) and wastewater pipe system (Gomez-Alvarez et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, some archaeal groups in sludge, such as Thermoprotei and Thermoplasmata, may be better able to colonize onto the membrane during the initial stage of biofilm development. In previous studies, the Thermoprotei and Thermoplasmata have also been detected to form the biofilms in many different environmental sites, such as sulfide-rich cave wall (Macalady et al, 2007), acid mine drainage system (Justice et al, 2012) and wastewater pipe system (Gomez-Alvarez et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…The presence of archaea has been previously documented in numerous terrestrial carbonate caves (Northup et al, 2003;Chelius and Moore, 2004;Gonzalez et al, 2006;Macalady et al, 2007;Legatzki et al, 2011), but their physiological role has remained elusive. This metagenomic analysis strongly suggests that Thaumarchaeota represent a second group of nitrification-based primary producers in Kartchner Caverns.…”
Section: Discussionmentioning
confidence: 99%
“…Archaeal communities in cave systems, in general, have not been studied in detail. Macalady et al, (2007) showed that the dominant archaea in the wall biofilms from Frasassi Cave (another chemoautotrophy-based cave, but with a low pH) were associated with two groups, namely Ferroplasma and an environmental clone group with sequences from acid mine drainage and Yellowstone hot spring. No Crenarchaeota were found in Frasassi Cave.…”
Section: Sulfur/ammonia-oxidizing Bacteria In Movile Cavementioning
confidence: 99%